CONSTRUCTION OF PROSOCIAL EMPATHY VALUES THROUGH PROJECT BASED LEARNING METHODS BASED ON SOCIAL EXPERIMENTS (STUDY OF DISCOVERING CULTURAL THEMES IN THE SUMBER-CIREBON SOCIETY) - Aiman Faiz; Purwati Purwati; Imas Kurniawaty (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
AbstractThe article aims to explore prosocial values in the middle and lower economic community in Sumber still exist. To describe it, the Project Based Learning method with the social experimental concept is a way of exploring the existing conditions through the role of students of the Muhammadiyah University of Cirebon.The research method in this study is a descriptive method with a qualitative approach. data collection using observation and interviews. Results of the study describe, middle and lower economic communities still have high prosocial value to others. Although these (research objects) are middle to lower class people, their prosocial behavior skills are quite good. There is a driving force through empathy, emotional maturity, moral rule orientation, and self interest that underlie the objects of research to do good. Another influence, is extrinsic motivation resulting from the response of sight, hearing, heart and feelings as well as cognitive processes within the object being the main factor in doing good. For them helping others without expecting anything in return is a pleasant thing, they believe Allah will reward what they do to others. Thus, the interpersonal skills and prosocial behavior of the middle and lower classes in Sumber Kabupaten Cirebon have good results.Keywords: Prosocial values, empathy, project based learning, social experimentsAbstrak Artikel bertujuan untuk mengeksplore apakah nilai-nilai prososial di masyarakat ekonomi menengah kebawah di Sumber masih ada. Untuk mendeskripsikannya metode Project Based Learning dengan konsep sosial eksperimen menjadi media dalam menggali kondisi yang ada melalui peran mahasiswa Universitas Muhammadiyah Cirebon. Adapun metode penelitian pada penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dengan observasi dan wawancara. Setelah data ditemukan, data kemudian di reduksi, disajikan dan di verifikasi untuk mendapatkan simpulan. Hasil penelitian mendeskripsikan, masyarakat ekonomi menengah kebawah masih memiliki nilai prososial yang tinggi terhadap orang lain. Kendati para (objek penelitian) ini orang-orang menengah kebawah, namun kemampuan prososial behaviour mereka cukup baik. Selain itu, adanya daya pendorong melalui empati, kematangan emosi, moral rule orientation, dan self interest yang mendasari para objek penelitian melakukan kebajikan. Pengaruh lain, adalah motivasi ekstrinsik yang dihasilkan dari respon penglihatan, pendengaran, hati dan perasaan juga proses kognitif didalam diri objek menjadi faktor utama dalam melakukan kebaikan. Membantu orang lain tanpa mengharapkan balasan bagi mereka adalah hal yang menyenangkan, mereka meyakini Allah akan membalas apa yang mereka lakukan pada orang lain. Dengan demikian, kemampuan interpersonal dan prososial behaviour masyarakat menengah kebawah di Sumber Kabupaten Cirebon hasilnya cukup baik.Kata kunci: Nilai prososial, empati, project based learning, sosial eksperimen